Russia's new authoritarianism : Putin and the politics of order - Lewis, David, 1967- (Edinburgh University Press, 2020)
David G. Lewis explores the transformation of Russian domestic politics and foreign policy under Vladimir Putin. Using contemporary case studies - including Russia's legal system, the annexation of Crimea and Russian policy in Syria - he critically examines Russia's new authoritarian political ideology.